Numerical study on steel-concrete composite floor systems under corner column removal scenario. (October 2019) - Fu, Qiuni; Tan, Kang-Hai
Abstract: In this paper, the authors assess the robustness of steel-concrete composite floor systems subjected to a Corner Column (CC) removal scenario based on numerical simulations. First, a modelling method is verified by previous actual test results conducted by the authors. Afterwards, using the reliable modelling method a composite floor system subjected to a corner column loss is simulated, producing the static load-displacement curve, the failure mode and load-transfer mechanisms. These results are compared with those of composite floor systems under an Internal Column (IC) removal scenario. Besides, the model is applied to simulate that the same composite floor system experiences a sudden column removal under six levels of loads. The dynamic displacement-time histories under all levels of loads are obtained, from which the loads and corresponding maximum deflections constitute the dynamic load-deflection response. They are used to evaluate the dynamic load capacity and deformability of this composite floor system subjected to a sudden CC removal scenario. Lastly, Dynamic Increase Factors (DIFs) are obtained through comparing the dynamic load-deflection response with the quasi-static one, which are further compared with DIFs under IC scenario.